Influence of chitosan coating on the oral bioavailability of gold nanoparticles in rats - Ahmed Alalaiwe; Paul Carpinone; Saad Alshahrani; Bader Alsulays; Mohammed Ansari; Mohammed Anwer; Sultan Alshehri; Abdullah Alshetaili (Elsevier, 2019)
Gold nanoparticles are one of the most extensively investigated metallic nanoparticles for several applications. It is less toxic than other metallic nanolattices. The exceptional electrical and thermal conductivity of gold make it possible to be administered as non-invasive radiofrequency irradiation therapy that produces sufficient heat to kill tumor cells. Nanoparticles are generally administered intravenously instead of orally due to negligible oral absorption and cellular uptake. This study evaluated the oral bioavailability of gold nanoparticles coated with chitosan (C-AuNPs), a natural mucoadhesive polymer. We employed traditional method of evaluating bioavailability that involve estimation of maximum concentrations and area under the curve of 3 nm chitosan coated gold nanoparticles (C-AuNPs) in the rat plasma following intravenous and oral administrations (0.8 mg and 8 mg/kg body weight respectively). The oral bioavailability of C-AuNPs was found to be 2.46% (approximately 25 folds higher than polyethylene glycol (PEG) coated gold nanoparticles, reported earlier). These findings suggest that chitosan coating could be better than PEG coating for the enhancement of oral bioavailability of nanoparticles. Keywords: Chitosan, Gold nanoparticles (AuNP), Chitosan coated gold nano-particles (C-AuNP), Bioavailability, Rat plasma, Area under curve